Structure of the human cation–chloride cotransporter NKCC1 determined by single-particle electron cryo-microscopy - Xiaoyong Yang (Nature Portfolio, 2020)
The human NKCC1 transporter belongs to the cation–chloride cotransporter (CCC) family and has important physiological functions, among them the regulation of chloride homeostasis and neuronal excitability. Here the authors present the 3.46 Å cryo-EM structure of human NKCC1 in a in a partially loaded, inward-open state and discuss the transport mechanism.